2021
DOI: 10.3390/antibiotics10040399
|View full text |Cite
|
Sign up to set email alerts
|

New Functionalized Macroparticles for Environmentally Sustainable Biofilm Control in Water Systems

Abstract: Reverse osmosis (RO) depends on biocidal agents to control the operating costs associated to biofouling, although this implies the discharge of undesired chemicals into the aquatic environment. Therefore, a system providing pre-treated water free of biocides arises as an interesting solution to minimize the discharge of chemicals while enhancing RO filtration performance by inactivating bacteria that could form biofilms on the membrane system. This work proposes a pretreatment approach based on the immobilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
1
2
0
Order By: Relevance
“…It is important to note that the PI uptake percentages observed for C − (18-21%) are consistent with data reported in the literature (Fernandes et al, 2020;Barros et al, 2021). The question why live cells can be stained with PI remains unanswered (Shi et al, 2007).…”
Section: Effect Of Biocides On Membrane Integritysupporting
confidence: 86%
See 1 more Smart Citation
“…It is important to note that the PI uptake percentages observed for C − (18-21%) are consistent with data reported in the literature (Fernandes et al, 2020;Barros et al, 2021). The question why live cells can be stained with PI remains unanswered (Shi et al, 2007).…”
Section: Effect Of Biocides On Membrane Integritysupporting
confidence: 86%
“…The LIVE/DEAD ® Baclight™ kit (Invitrogen) was used to assess membrane integrity of bacterial cells after exposure to biocides. In brief, an aliquot of 1 mL was filtered through a 0.2-μm Nucleopore ® (Whatman) black polycarbonate membrane and stained with 250 μl of SYTO9™ and 50 μl of propidium iodide (PI) in the dark (Barros et al, 2021). After reacting for 7 min, the stains were filtered and the samples mounted on a slide with immersion oil.…”
Section: Membrane Integritymentioning
confidence: 99%
“…However, when reusing the Al 2 O 3 -DA-BAC particles, a higher contact time was needed to reach total inactivation. The authors concluded that Al 2 O 3 -DA-BAC particles are a suitable antimicrobial agent for the treatment of continuous water systems with minimal environmental and health impacts [ 7 ].…”
mentioning
confidence: 99%